Gold electrode conductive paste and electronic circuit

By fusing the micron oxide and nanooxide to form a composite powder and combining with sheet-shaped micron gold powder, the problems of sintering density and reliability of the gold electrode conductive paste are solved, and efficient sintering and chemical stability are achieved.

CN119724680AActive Publication Date: 2025-03-28JINGLAN ADVANCED MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510220569.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-28
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

The existing gold electrode conductive paste is difficult to take into account both low defect density and sintering densification during the sintering process, resulting in reduced reliability and insufficient sintering of glass powder flowing at high temperatures.

Method used

Micron oxides and nanooxides are fused through a high-speed mixing and fusion machine to form a composite powder and a sheet-shaped micron gold powder. The low melting temperature of the nanooxide and the eutectic effect of the oxide interface are used to generate a local liquid phase, and the sintering of the oxide and the gold powder is completed.

Benefits of technology

The sintering density of gold electrodes is improved, the phenomenon of bulging is eliminated, the reliability and chemical stability of the circuit are improved, and the working environment is adapted to high-temperature and high-power.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides gold electrode conductive paste and an electronic circuit. The conductive paste comprises 50-90 wt% of gold powder, 1-20 wt% of composite powder and 5-30 wt% of an organic carrier. Wherein the gold powder is in a micron sheet shape, and the composite powder is formed through high-speed fusion heat and impact, takes a micron oxide as a core and is coated with a nano oxide surface layer. The special composite powder is matched with the micron flaky gold powder, oxides in the composite powder do not flow in the sintering process of slurry, but are uniformly distributed in gaps of the flaky gold powder, the low melting temperature characteristic of the surface nanometer oxides and a local liquid phase generated by the eutectic effect of the interfaces of the two oxides are utilized, and the surface of the micron flaky gold powder is sintered. The high requirements of sintering compactness (low resistivity and no falling) and chemical stability are met at the same time, the contact area between the flaky micron gold powder and the spherical micron gold powder is large, and the flaky micron gold powder and the spherical micron gold powder are used in cooperation with the special composite powder, so that the sintering compactness is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic circuits, and in particular to a gold electrode conductive slurry and an electronic circuit prepared by using the slurry. Background Art

[0002] Gold paste is used as an electrode paste in electronic circuits that require high reliability or are related to biomedicine, such as military radar components, high-frequency communications, and medical plasma lamps, due to its conductivity similar to that of silver, chemical stability far superior to silver (it does not react with elements in the air to oxidize or sulfide), biocompatibility, and resistance to electromigration.

[0003] However, due to the chemical stability of gold, it is difficult for gold powder to take into account the contradiction between low defect density and sintering densification through its own preparation process and morphology. Nanoscale spherical gold powder (<1um) has a high degree of sintering densification, but it has many defects, which will reduce the reliability of gold paste. The use of micron-scale (>1um) spherical or flaky gold powder has fewer defects, but it is difficult to sinter and densify, and has poor conductivity, so glass powder is more needed to assist sintering. In addition, due to the high adhesion requirements between metal and quartz glass or ceramic substrates, glass powder is usually required as a sintering binder. When glass powder is matched with gold powder, the surface energy of the glass powder is reduced after melting at high temperature, which will cause the nano-gold powder to form bulges during the sintering process. If micron gold powder is used, although the stability of micron gold powder is better and it is not easy to bulge, the glass powder will flow after softening at high temperature. Due to the action of gravity, it will flow to the surface of the substrate and cannot fill the gaps between the micron gold powders. It cannot promote the sintering between the micron gold powders. In addition, due to the high chemical activity of glass powder, in a high-power working environment, an oxidation reaction will occur due to high temperature or current, which will destroy the antioxidant ability of the gold powder itself.

[0004] Compared with glass, oxides have strong chemical stability, but because their melting temperatures are usually above 1000°C, while the sintering temperatures of metals are all below 1000°C, oxides cannot participate in the sintering and densification of metals. Although oxides can reduce the melting temperature and participate in sintering when they reach the nanoscale, the specific surface area of ​​nano oxides is too high, which will greatly increase the viscosity of the slurry and cannot be made into a slurry suitable for screen printing under normal usage. Summary of the invention

[0005] In view of the defects in the prior art, the purpose of the present invention is to provide a gold electrode conductive paste and an electronic circuit prepared using the paste, wherein a special composite powder is combined with flaky micron gold powder to simultaneously improve the sintering density of the gold electrode, eliminate bulging, and improve reliability.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] According to a first aspect of the present invention, there is provided a gold electrode conductive paste, characterized in that it comprises the following components in terms of mass percentage:

[0008] 50~90wt% gold powder, 1~20wt% inorganic powder, and 5~30wt% organic carrier;

[0009] The gold powder is a flaky micron gold powder, the short diameter of the flaky micron gold powder is 1-3um, and the long diameter is 2-30um;

[0010] The inorganic powder is a composite powder prepared in the following manner:

[0011] S1. Weigh micron oxide and nano oxide in any ratio of 9:1 to 1:1, grind and dry to obtain a mixed powder;

[0012] S2, adding the mixed powder into a high-speed mixing and fusion machine and mixing at a speed not less than 1000 rpm to obtain fused powder;

[0013] S3, crushing and classifying the fused powder to obtain a composite powder with nano-oxide particles coated on the surface of micro-oxide;

[0014] The particle size of the micron oxide is 0.9-15um; the particle size of the nano oxide is 50-500nm.

[0015] In this technical solution, micron oxide and nano oxide are used, and the nano oxide is melted and embedded in the surface of the micro oxide through the heat and impact of high-speed fusion, and the surface of the powder is sphericalized by impact to make a composite powder with micro oxide as the core and coated with a nano oxide surface layer. The composite powder is used in combination with micron flaky gold powder for the preparation of gold electrode conductive paste. During the sintering process of the paste, the low melting temperature characteristics of the surface nano oxide and the local liquid phase produced by the eutectic effect of the interface of the two oxides are used to complete the sintering of the oxide and the gold powder. Optionally, in step S3 of this technical solution, the fused powder is crushed and graded, and the particle size of the obtained composite powder is 1~15um, preferably 1~5um; further, regarding the size of the micron flaky gold powder in this technical solution, its short diameter can also be understood as the thickness of the flaky gold powder, and the long diameter can also be understood as the diameter of the flaky gold powder.

[0016] Preferably, the short diameter of the flaky micron gold powder is 1-2 um, and the long diameter is 3-6 um.

[0017] Preferably, the flaky micron gold powder is obtained by annealing at 400° C. for 2 hours in argon protection.

[0018] Preferably, the micron oxide is any one of the following: aluminum oxide, zirconium oxide, magnesium oxide, silicon oxide, calcium oxide, titanium oxide, and mullite;

[0019] The nano oxide is any one or more of the following: lead oxide, boron oxide, zinc oxide, barium oxide, copper oxide, silver oxide, bismuth oxide, iron oxide, nickel oxide, cerium oxide, germanium oxide, manganese oxide, and tin oxide.

[0020] The composite powder in the present technical solution has good adaptability and is very flexible in adjusting the matching substrate and components. For example, if the substrate is a quartz substrate, micron silicon oxide is selected as the core, and if it is a ceramic substrate, micron aluminum oxide is selected as the core, and the surface component ratio can be adjusted by the mixing ratio of the nanopowder.

[0021] Preferably, the micron oxide is silicon oxide, and the nano oxide is bismuth oxide and / or zinc oxide.

[0022] Preferably, the silicon oxide is mesoporous silicon oxide.

[0023] In the present technical solution, mesoporous silica is more easily embedded with nanopowder to achieve the technical effect described in the present application.

[0024] Preferably, the micron oxide and the nano oxide are weighed in a ratio of 7:1 to 3:1.

[0025] Preferably, in step S2, the mixed powder is added into a high-speed mixing and fusion machine and mixed at a speed of 1000-30000 rpm for 1-30 min.

[0026] Preferably, in step S2, the mixed powder is added into a high-speed mixing and fusion machine and mixed at a speed of 5000-10000 rpm for 1-10 min.

[0027] Preferably, the particle size of the micron oxide is 1-4.5 um, and the particle size of the nano oxide is 100-200 nm.

[0028] According to a second aspect of the present invention, there is provided an electronic circuit, which is prepared using the gold electrode conductive paste described in the first aspect of the present invention.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The gold electrode conductive paste provided by the present invention adopts micron oxide and nano oxide, and embeds the nano oxide on the surface of the micro oxide through the heat and impact of high-speed fusion, and sphericalizes the surface of the powder through impact, so as to prepare a composite powder with micron oxide as the core and coated with a nano oxide surface layer. The composite powder is matched with micron flaky gold powder. During the sintering process of the paste, the oxide does not flow, but is evenly distributed in the gaps of the flaky gold powder. The low melting point of the surface nano oxide and the local liquid phase produced by the eutectic effect of the interface of the two oxides are utilized to complete the sintering of the oxide and the gold powder, thereby achieving the high requirements of sintering density (low resistivity, no shedding) and chemical stability at the same time. Compared with the spherical micron gold powder, the flaky micron gold powder has a large contact area between the powders, and the use of the composite powder can achieve better sintering density.

[0031] 2. The gold electrode conductive paste provided by the present invention, in which the specially prepared composite powder can be fully matched with the flaky gold powder, not only has strong adaptability, but also is very flexible in adjusting the matching substrate and components (for example, if the substrate is a quartz substrate, micron silicon oxide is selected as the core, if it is a ceramic substrate, micron aluminum oxide is selected as the core, and the surface component ratio can be adjusted by the mixing ratio of nano powders), and also has the high reliability and chemical stability of oxides, and can complete normal slurry sintering, which greatly improves the performance of gold paste in forming electronic circuits on the surface of quartz glass and densified ceramics, and can simultaneously meet the requirements of low resistance and low loss, and adapt to high temperature and high power reliability. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0033] Example 1

[0034] 250 g of 1 um mesoporous silicon oxide and 100 nm bismuth oxide are weighed in a ratio of 3:1, added into an agate grinding jar, 250 g of water and 250 g of 10 mm agate grinding balls are added, ground at 200 rpm for 10 min, and dried at 110° C. for 1 hr to obtain a mixed powder; the mixed powder is added into a high-speed mixing and fusion machine and mixed at 8000 rpm for 10 min to obtain a fused powder; the fused powder is added into a jet mill for pulverization and classification to obtain a composite powder with a particle size of 1-2 um, wherein the composite powder is in the form of nano-bismuth oxide particles coated on the surface of micron silicon oxide.

[0035] Then, prepare the gold electrode conductive slurry according to the following method:

[0036] S1. First, weigh 4 g of the composite powder prepared above and 9 g of the organic carrier, put the composite powder and the organic carrier into a wide-mouth bottle of a planetary mixer, stir them evenly with a spatula, mix them at 800 rpm for 3 min with a planetary mixer, and then grind them 4 times with a three-roll grinder. The grinding fineness is tested to be less than 5 μm, and a uniform mixed solution is obtained;

[0037] S2, adding 87 g of gold powder (micron flake gold powder with a short diameter D50 of 1 um and a long diameter D50 of 4.5 um) to the mixed solution obtained in step S1, and stirring evenly with a spatula; then mixing with a planetary mixer at a speed of 800 rpm for 3 min to obtain a sample slurry;

[0038] S3. Grind the sample slurry obtained in S2 for 5 times using a three-roll grinder. Tests show that the grinding fineness is less than 10 μm and the Brookfield viscosity is between 150-200 Pa.s, thereby obtaining the gold electrode conductive slurry of this embodiment.

[0039] In step S1, the organic carrier is a mixture of ethyl cellulose, butyl carbitol acetate and methyl ester-12 in a mass ratio of 1.5:2.7:2.7.

[0040] Example 2

[0041] The gold electrode conductive paste was prepared in the same manner as in Example 1, with the only difference being that in the preparation of the composite powder in this example, the mixing ratio of 1 um mesoporous silicon oxide and 100 nm bismuth oxide was 3.5:0.5.

[0042] Example 3

[0043] The gold electrode conductive paste was prepared in the same manner as in Example 1, with the only difference being that in the preparation of the composite powder in this example, the mixing ratio of 1 um mesoporous silicon oxide and 100 nm bismuth oxide was 3.9:0.1.

[0044] Example 4

[0045] The gold electrode conductive paste was prepared by the same method as in Example 1, with the only difference being that when preparing the composite powder in this example, the nano oxides were nano bismuth oxide and nano zinc oxide, and the mixing ratio of 1 um mesoporous silicon oxide, 100 nm bismuth oxide, and 100 nm zinc oxide was 3:0.5:0.5.

[0046] Example 5

[0047] The gold electrode conductive paste was prepared by the same method as in Example 1, with the only difference being that when preparing the composite powder in this example, the nano oxides were nano bismuth oxide and nano zinc oxide, and the mixing ratio of 1 um mesoporous silicon oxide, 100 nm bismuth oxide, and 100 nm zinc oxide was 3.5:0.4:0.1.

[0048] Example 6

[0049] The gold electrode conductive paste was prepared in the same manner as in Example 1, with the only difference being that in preparing the composite powder in this example, the nano oxide was nano zinc oxide, and the mixing ratio of 1 um mesoporous silicon oxide and 100 nm zinc oxide was 3.9:0.1.

[0050] Comparative Example 1

[0051] It is the commercially available DuPont 5771 gold paste, which uses nano-spherical gold powder with an inorganic component content of about 2.5%, wherein the glass powder contains Si, Al, Pb, Zn, Bi and other elements.

[0052] Comparative Example 2

[0053] Weigh 250g of 1um mesoporous silica and 1um bismuth oxide in a ratio of 3:1, add them into an agate grinding jar, add 250g of water and 250g of 10mm agate grinding balls, grind at 200rpm for 10min, dry at 110℃ for 1hr, then add to a high-speed mixer and mix at 8000rpm for 10min, and then add to a jet mill for crushing and grading to obtain a mixed powder.

[0054] Then, prepare the gold electrode conductive slurry according to the following method:

[0055] S1. First, weigh 4 g of the mixed powder prepared above and 9 g of the organic carrier, put the mixed powder and the organic carrier into a wide-mouth bottle of a planetary mixer, stir them evenly with a spatula, mix them at 800 rpm for 3 min with a planetary mixer, and then grind them 4 times with a three-roll grinder. The grinding fineness is tested to be less than 5 μm, and a uniform mixed solution is obtained;

[0056] S2, adding 87g of gold powder (micron flake gold powder with a short diameter D50 of 1um and a long diameter D50 of 4.5um) to the mixed solution obtained in step S1, and stirring evenly with a spatula; then mixing with a planetary mixer at a speed of 800rpm for 3min to obtain a sample slurry;

[0057] S3. Grind the sample slurry obtained in S2 for 5 times using a three-roll grinder. Tests show that the grinding fineness is less than 10 μm and the Brookfield viscosity is between 150-200 Pa.s, thereby obtaining the gold electrode conductive slurry of this embodiment.

[0058] In step S1, the organic carrier is a mixture of ethyl cellulose, butyl carbitol acetate and methyl ester-12 in a mass ratio of 1.5:2.7:2.7.

[0059] Comparative Example 3

[0060] S1. Weigh 4 g of 1 μm mesoporous silica and 1 μm bismuth oxide, and 9 g of an organic carrier in a ratio of 3:1, put the aforementioned weighed silica, bismuth oxide and organic carrier into a wide-mouth bottle of a planetary mixer, stir them evenly with a spatula, mix them at 800 rpm for 3 min with a planetary mixer, and then grind them 4 times with a three-roll grinder. The grinding fineness is tested to be less than 5 μm, and a uniform mixed solution is obtained;

[0061] S2, adding 87g of gold powder (micron flake gold powder with a short diameter D50 of 1um and a long diameter D50 of 4.5um) to the mixed solution obtained in step S1, and stirring evenly with a spatula; then mixing with a planetary mixer at a speed of 800rpm for 3min to obtain a sample slurry;

[0062] S3. Grind the sample slurry obtained in S2 for 5 times using a three-roll grinder. Tests show that the grinding fineness is less than 10 μm and the Brookfield viscosity is between 150-200 Pa.s, thereby obtaining the gold electrode conductive slurry of this embodiment.

[0063] In step S1, the organic carrier is a mixture of ethyl cellulose, butyl carbitol acetate and methyl ester-12 in a mass ratio of 1.5:2.7:2.7.

[0064] Comparative Example 4

[0065] S1. Weigh 4 g of 1 um mesoporous silica and 100 nm bismuth oxide, and 9 g of an organic carrier in a ratio of 3.5:0.5, put the weighed mesoporous silica, bismuth oxide and organic carrier into a wide-mouth bottle of a planetary mixer, stir them evenly with a spatula, mix them at 800 rpm for 3 min with a planetary mixer, and then grind them 4 times with a three-roll grinder. The grinding fineness is tested to be less than 5 μm, and a uniform mixed solution is obtained;

[0066] S2, adding 87g of gold powder (micron flake gold powder with a short diameter D50 of 1um and a long diameter D50 of 4.5um) to the mixed solution obtained in step S1, and stirring evenly with a spatula; then mixing with a planetary mixer at a speed of 800rpm for 3min to obtain a sample slurry;

[0067] S3. Grind the sample slurry obtained in S2 for 5 times using a three-roll grinder. Tests show that the grinding fineness is less than 10 μm and the Brookfield viscosity is between 150-200 Pa.s, thereby obtaining the gold electrode conductive slurry of this embodiment.

[0068] In step S1, the organic carrier is a mixture of ethyl cellulose, butyl carbitol acetate and methyl ester-12 in a mass ratio of 1.5:2.7:2.7.

[0069] Comparative Example 5

[0070] S1. Weigh 4 g of ASF-1330 glass powder (the main component of the glass powder is PbO-B2O3 system, D50 is 2 um) produced by Asahi Glass Co., Ltd. of Japan, and 9 g of an organic carrier, put the glass powder and the organic carrier into a wide-mouth bottle of a planetary mixer, stir them evenly with a spatula, mix them at 800 rpm for 3 min with a planetary mixer, and then grind them 4 times with a three-roll grinder. The grinding fineness is tested to be less than 5 μm, and a uniform mixed solution is obtained;

[0071] S2, adding 87g of gold powder (micron flake gold powder with a short diameter D50 of 1um and a long diameter D50 of 4.5um) to the mixed solution obtained in step S1, and stirring evenly with a spatula; then mixing with a planetary mixer at a speed of 800rpm for 3min to obtain a sample slurry;

[0072] S3. Grind the sample slurry obtained in S2 for 5 times using a three-roll grinder. Tests show that the grinding fineness is less than 10 μm and the Brookfield viscosity is between 150-200 Pa.s, thereby obtaining the gold electrode conductive slurry of this embodiment.

[0073] In step S1, the organic carrier is a mixture of ethyl cellulose, butyl carbitol acetate and methyl ester-12 in a mass ratio of 1.5:2.7:2.7.

[0074] Comparative Example 6

[0075] 250 g of 1 um mesoporous silicon oxide and 100 nm bismuth oxide are weighed in a ratio of 3.5:0.5, added into an agate grinding jar, 250 g of water and 250 g of 10 mm agate grinding balls are added, ground at 200 rpm for 10 min, and dried at 110° C. for 1 hr to obtain a mixed powder; the mixed powder is added into a high-speed mixing and fusion machine and mixed at 8000 rpm for 10 min to obtain a fused powder; the fused powder is added into a jet mill and pulverized and classified to obtain a composite powder with a particle size of 1-2 um, wherein the composite powder is in the form of nano-bismuth oxide particles coated on the surface of micron silicon oxide.

[0076] Then, prepare the gold electrode conductive slurry according to the following method:

[0077] S1. First, weigh 4 g of the composite powder prepared above and 9 g of the organic carrier, put the composite powder and the organic carrier into a wide-mouth bottle of a planetary mixer, stir them evenly with a spatula, mix them at 800 rpm for 3 min with a planetary mixer, and then grind them 4 times with a three-roll grinder. The grinding fineness is tested to be less than 5 μm, and a uniform mixed solution is obtained;

[0078] S2, weigh 87 g of 800 nm spherical gold powder and add it to the mixed solution obtained in step S1, and stir it evenly with a spatula; then use a planetary mixer to mix it at a speed of 800 rpm for 3 minutes to obtain a sample slurry;

[0079] S3. Grind the sample slurry obtained in S2 for 5 times using a three-roll grinder. Tests show that the grinding fineness is less than 10 μm and the Brookfield viscosity is between 150-200 Pa.s, thereby obtaining the gold electrode conductive slurry of this embodiment.

[0080] In step S1, the organic carrier is a mixture of ethyl cellulose, butyl carbitol acetate and methyl ester-12 in a mass ratio of 1.5:2.7:2.7.

[0081] Table 1 shows the formula of the gold electrode conductive paste in the above examples and comparative examples 2 to 6:

[0082] Table 1

[0083]

[0084] Tables 2 and 3 show the selection of gold powder, the formula of inorganic substances and the presence or absence of a running-in process in the above embodiments and comparative examples, wherein "Y" in the running-in process means "Yes", which means there is a running-in process, and "N" means "NO", which means there is no running-in process. The so-called running-in process refers to the process of fusing oxides through a high-speed mixing and fusion machine; at the same time, the proportion of the series substances shown in the following table, such as the ratio of micron silicon oxide to nano bismuth oxide in embodiment 1 is 3:1, and the ratio of glass powder in comparative example 1 is 2.5, indicating that the inorganic substances are all glass powders, and do not contain other micron and nano oxides;

[0085] Table 2

[0086]

[0087] Table 3

[0088]

[0089] Furthermore, the gold electrode conductive pastes of the above embodiments and comparative examples were screen-printed on quartz glass sheets using a screen (a 10 μm thick steel plate mesh with a pattern design of 5 cm long and 250 μm wide grid lines, forming a parallel array with an interval of 2 mm), and dried in an oven at 200° C. for 10 min. The dried quartz glass sheets were placed in a muffle furnace with a set temperature of 700° C. and a sintering time of 20 min for subsequent testing.

[0090] Test method:

[0091] The number of bulges and the degree of discoloration are observed with the naked eye.

[0092] The adhesion test is to tear the tape with 3M tape, and it is qualified if 100% of it does not fall off.

[0093] Resistance test: Select 5 gate lines at different positions, use the SP1103W-sek profiler from Will Company, select 3 points at different positions of each gate line to measure the gate line thickness and take the average value, unit um. Use an ohmmeter to measure the resistance of the 5 gate lines and take the average value, unit mohm. Calculate the sheet resistivity (unit: mohm / □) ​​using the following calculation formula: (resistance*thickness) / (200*standard thickness 5um).

[0094] Aging test: The gold electrode was loaded with 3kV, 40kHZ high voltage and high frequency for 120 hours.

[0095] Tables 4 and 5 show the experimental data, where the unit of sheet resistivity is mohm / □.

[0096] Table 4

[0097]

[0098] Table 5

[0099]

[0100] According to the above experimental data, we can know that:

[0101] Comparative Example 1 uses commercially available gold paste. Since it uses glass powder and nano-spherical gold powder, it has better sintering performance, lower sheet resistivity and better adhesion. However, due to the poor chemical stability of glass powder, the defects of nano-spherical gold powder itself, and the high reactivity of both, bulging will form after sintering, and bulging, discoloration, and falling off will occur after aging. The embodiments provided in this application, through the combination of special composite oxide powder and flaky gold powder, have no problems such as bulging, discoloration, and falling off.

[0102] Although Comparative Examples 2 and 3 also use micron-sized flake gold powder, since the inorganic components used are only micron-sized oxides, sintering cannot be achieved regardless of whether a running-in process is used.

[0103] Although Comparative Example 4 also uses micron-shaped flake gold powder, and the inorganic components also use micron oxides and nano oxides, since no running-in process is used, the nano oxide added alone will seriously affect the printing performance of the slurry, and the sheet resistivity is relatively high; and since the reaction activity of the nano oxide is relatively strong compared to the micro oxide, it will cause local failure problems during the aging process.

[0104] Comparative Example 5 uses micron flake gold powder. Due to its low sintering activity, no bulging will occur when it is sintered with glass powder. This is a characteristic of flake gold powder. However, since the glass powder will all flow to the surface of the substrate and cannot promote sintering densification, the sheet resistivity of Comparative Example 5 is nearly twice that of Comparative Example 6 using spherical gold powder. In addition, during the aging process, the activity of the glass powder will still lead to aging problems such as grid line shedding and black spots.

[0105] Although Comparative Example 6 uses a special composite powder, its gold powder is nano-spherical gold powder. Since both nano-spherical gold powder and composite powder are conducive to sintering, the gold paste after sintering has good performance in various aspects, and the sheet resistivity is in the median (since there are more defects in the spherical powder, the sheet resistivity is slightly higher than the same type of optimized micron sheet gold powder samples). However, during the aging process, the composite powder cannot completely overcome the problems caused by the defects of the nano-spherical gold powder, so there will be bulging, blackening and a sharp increase in sheet resistivity. Only the adhesion is still qualified.

[0106] The performance variation pattern between Examples 1 to 6 provided in the present application is as follows: in Examples 4 and 5, two different nano-oxides are added when preparing the composite powder, while in other Examples only one nano-oxide is added, and the sheet resistivity of Examples 4 and 5 is lower than that of the other Examples, because the addition of different nano-oxides can moderately reduce the surface melting temperature of the composite powder, improve the sintering density, and form a better sheet resistivity; in Example 1 and Example 4, the addition ratio of nano-oxide is higher than that of other Examples, and the sheet resistivity attenuation rate of Example 1 and Example 4 is higher than that of other Examples, indicating that the addition of too much nano-oxide will reduce the aging performance, which needs to be balanced; but the aging performance of all composite powders is better than that of the comparative examples, and the sheet resistivity is equivalent to that of the glass powder.

[0107] The above describes the specific embodiments of the present invention. Based on the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention.

Claims

1. A gold electrode conductive paste, characterized in that: The following components are included in terms of mass percentage: 50~90wt% gold powder, 1~20wt% inorganic powder, and 5~30wt% organic carrier; The gold powder is a flaky micron gold powder, the short diameter of the flaky micron gold powder is 1-3um, and the long diameter is 2-30um; The inorganic powder is a composite powder prepared in the following manner: S1. Weigh micron oxide and nano oxide in any ratio of 9:1 to 1:1, grind and dry to obtain a mixed powder; S2, adding the mixed powder into a high-speed mixing and fusion machine and mixing at a speed not less than 1000 rpm to obtain fused powder; S3, crushing and classifying the fused powder to obtain a composite powder with nano-oxide particles coated on the surface of micro-oxide; The particle size of the micron oxide is 0.9-15um; the particle size of the nano oxide is 50-500nm.

2. The gold electrode conductive paste according to claim 1, characterized in that: The short diameter of the flaky micron gold powder is 1-2 um, and the long diameter is 3-6 um.

3. The gold electrode conductive paste according to claim 1, characterized in that: The flaky micron gold powder is obtained by annealing at 400° C. in argon protection for 2 hours.

4. The gold electrode conductive paste according to claim 1, characterized in that: The micron oxide is any one of the following: aluminum oxide, zirconium oxide, magnesium oxide, silicon oxide, calcium oxide, titanium oxide, and mullite; The nano oxide is any one or more of the following: lead oxide, boron oxide, zinc oxide, barium oxide, copper oxide, silver oxide, bismuth oxide, iron oxide, nickel oxide, cerium oxide, germanium oxide, manganese oxide, and tin oxide.

5. The gold electrode conductive paste according to claim 4, characterized in that: The micron oxide is silicon oxide, and the nano oxide is bismuth oxide and / or zinc oxide.

6. The gold electrode conductive paste according to claim 5, characterized in that: The silicon oxide is mesoporous silicon oxide.

7. The gold electrode conductive paste according to claim 1, characterized in that: In step S1, micron oxide and nano oxide are weighed in any ratio of 7:1 to 3:

1.

8. The gold electrode conductive paste according to claim 1, characterized in that: In step S2, the mixed powder is added into a high-speed mixing and fusion machine and mixed at a speed of 1000-30000 rpm for 1-30 min.

9. The gold electrode conductive paste according to claim 1, characterized in that: In step S2, the mixed powder is added into a high-speed mixing and fusion machine and mixed at a rotation speed of 5000-10000 rpm for 1-10 minutes.

10. The gold electrode conductive paste according to claim 1, characterized in that: The particle size of the micron oxide is 1-4.5 um, and the particle size of the nano oxide is 100-200 nm.

11. An electronic circuit, characterized in that: The gold electrode conductive paste is prepared using the gold electrode conductive paste according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Conductive paste, preparation method thereof and application of conductive paste in porous back electrode

    CN118942764A

  • Glass powder for conductive gold paste as well as preparation method and application of glass powder

    CN119143398A

  • Conductive slurry for solar battery and preparation method thereof

    US20120032120A1